2023
DOI: 10.3390/atmos15010045
|View full text |Cite
|
Sign up to set email alerts
|

Particle Number Size Distribution in Three Different Microenvironments of London

Gopinath Kalaiarasan,
Prashant Kumar,
Mamatha Tomson
et al.

Abstract: We estimated the particle number distributions (PNDs), particle number concentrations (PNCs), physicochemical characteristics, meteorological effects, and respiratory deposition doses (RDD) in the human respiratory tract for three different particle modes: nucleation (N6–30), accumulation (N30–300), and coarse (N300–10,000) modes. This study was conducted in three different microenvironments (MEs) in London (indoor, IN; traffic intersection, TI; park, PK) measuring particles in the range of 6 nm–10,000 nm usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Kalaiarasan at al. concluded that respiratory deposition doses and particle number concentrations can be applicable to investigate relationships between particle diameter and deposition in the different regions of the lungs, considering the impact of the UFP deposition in the deeper region of the lungs [26].…”
Section: Lung Deposited Surface Areamentioning
confidence: 99%
“…Kalaiarasan at al. concluded that respiratory deposition doses and particle number concentrations can be applicable to investigate relationships between particle diameter and deposition in the different regions of the lungs, considering the impact of the UFP deposition in the deeper region of the lungs [26].…”
Section: Lung Deposited Surface Areamentioning
confidence: 99%
“…In the modern age, people from every corner of the planet spend most of their time in indoor spaces [1][2][3][4][5][6][7][8][9], which makes the field of indoor air quality (IAQ) more relevant than ever. Furthermore, during the COVID-19 pandemic, a great challenge for the health of cities and societies, people experienced national lockdowns, which made them more vulnerable to massive exposure to indoor air pollution [5,6,10,11].…”
Section: Introductionmentioning
confidence: 99%